Distance Variation Approach in Elementary School Students: Learning Outcomes of Underhand Passing - Nur, Nirmawati; Fahrizal, Fahrizal; Suwardi, Suwardi; Hudain, Muh. Adnan; Adil, Ahmad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to enhance the learning outcomes of underhand passing in volleyball games by using a distance variation approach specifically designed for fifth-grade students at public elementary schools. The research method employs classroom action research, a one-cycle process that involves stages of planning, action, observation, and reflection. The subjects of the study were 22 fifth-grade students at Public Elementary School Parak No. 11 Kepulauan Selayar. The distance variation approach applied includes distances of 2 meters, 3 meters, and 4 meters with a focus on the assessment of accuracy (0-30), strength (0-30), and technique (0-40). The results of the study showed an increase in underhand passing ability from the initial condition, where 13 students were in the